2003
DOI: 10.1002/dvdy.10333
|View full text |Cite
|
Sign up to set email alerts
|

Wnt11 and Wnt7a are up‐regulated in association with differentiation of cardiac conduction cells in vitro and in vivo

Abstract: The heart beat is coordinated by a precisely timed sequence of action potentials propagated through cells of the conduction system. Previously, we have shown that conduction cells in the chick embryo are derived from multipotent, cardiomyogenic progenitors present in the looped, tubular heart. Moreover, analyses of heterogeneity within myocyte clones and cell birth dating have indicated that elaboration of the conduction system occurs by ongoing, localized recruitment from within this multipotent pool. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 44 publications
3
26
0
Order By: Relevance
“…Here we show that Wnt11 mRNA is present in various mouse tissues such as the heart and kidney as reported previously (50,78). The distribution of Wnt11 in these tissues corresponds well with its functions in the morphogenesis of cardiac myocytes (46) and differentiation of cardiac conduction cells (78) and kidney ureter (50,79). In the developing gastrointestinal tract, Wnt11 is localized in the endodermal layer of the esophagus and colon as well as in the mesenchymal layer of the stomach (20).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Here we show that Wnt11 mRNA is present in various mouse tissues such as the heart and kidney as reported previously (50,78). The distribution of Wnt11 in these tissues corresponds well with its functions in the morphogenesis of cardiac myocytes (46) and differentiation of cardiac conduction cells (78) and kidney ureter (50,79). In the developing gastrointestinal tract, Wnt11 is localized in the endodermal layer of the esophagus and colon as well as in the mesenchymal layer of the stomach (20).…”
Section: Discussionsupporting
confidence: 90%
“…The source and the nature of the Wnt signal in the intestinal crypt and whether a concentration gradient of Wnt secretion exists in the intestinal crypt are still largely undetermined. Here we show that Wnt11 mRNA is present in various mouse tissues such as the heart and kidney as reported previously (50,78). The distribution of Wnt11 in these tissues corresponds well with its functions in the morphogenesis of cardiac myocytes (46) and differentiation of cardiac conduction cells (78) and kidney ureter (50,79).…”
Section: Discussionsupporting
confidence: 89%
“…Heart valve formation Required (zebrafish, chicken) [96][97][98][99][100] Not known Development of conduction system Not known Expression but no functional data 121 The role of different aspects of the Wnt signaling network during cardiac differentiation and development are given as discussed in the text.…”
Section: Disclosuresmentioning
confidence: 99%
“…Beginning with the observations that peripheral and central conduction tissue derives from cardiomyocyte progenitors in the chick, 3,4 investigators have now identified key roles for many important molecular signals and transcription factors in conduction system development. Signaling molecules implicated in the formation of the conduction system include endothelin, [5][6][7][8][9] neuregulin, 10 -13 Wnts, 14 and bone morphogenetic proteins, 15 and complex transcriptional roles have been identified for NKx2.5, 16 -20 members the T-box transcription factor family, 18,21,22 shox2, 23 msx2, 24,25 and hop. 26 -28 In this issue of Circulation, Rentschler et al 29 take a significant step toward understanding the determinants of conduction cell fate.…”
Section: Article See P 1058mentioning
confidence: 99%